Pratiques nautiques en Bretagne : rivalités plurielles, représentations et pratiques en concurrence - Marion Florez (Projets de Paysage)
After observing the development and geographical spread of nature sports, the article focuses on the impacts of these sports on coastal areas in Brittany by using the example of the Bay of Audierne. Such coastal areas, rich in biodiversity and at the heart of nature conservation issues, are also used as levers for implementing policies for the development of tourism which are also reliant on sports. Based on a collection of statements made by inhabitants, sports practitioners, and the managers of natural spaces, this article attempts to analyse the interrelationships between the various groups of users sharing these spaces. Such interrelationships usually involve competition and rivalry thus constantly modifying the relationship each group has with the landscape and nature, constantly changing the ways they mark the landscape and the uses they make of these spaces.